KONSEP DASAR EVALUASI DALAM PEMBELAJARAN PENDIDIKAN ISLAM - Dewi Rahmayani; Julhadi Julhadi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Evaluation is an integral part of the learning process that functions to assess the extent to which educational objectives have been achieved. In the context of Islamic Religious Education (PAI), evaluation is not only oriented toward academic results but also toward the development of Islamic character, attitudes, and personality. This article aims to explain the basic concept of evaluation, including its definition, the relationship among testing, measurement, assessment, and evaluation, as well as the importance of evaluation in PAI learning. This study employs a qualitative method with a literature review approach based on the theories of Arikunto, Tyler, Sudijono, and Muhaimin. The findings indicate that evaluation is a systematic and continuous process for assessing both the learning process and outcomes across three main domains: cognitive, affective, and psychomotor. In Islam, evaluation has a theological foundation through the concept of muhasabah (self-reflection), which guides educators and learners to continually improve themselves. Therefore, evaluation serves as an essential instrument for realizing quality, equitable, and Islamic character-based education.Keywords: Evaluation, Test, Measurement, Assessment, Islamic Religious Education